Learning about our environment
Using striking photography, this multimedia CD familiarizes students with patterns of population growth, competition, cooperation, specialization, and succession. Topics include: energy and the food chain, plants and animals in community; ecology and conservation; effects of industrialization, urbanization, and modernization; and human beings and the environment.